A destructive host-shift : a comparative review of resistance mechanisms in the novel and original hosts of Varroa destructor - Sjögren Englund, Elin (SLU/Dept. of Ecology, 2022)
Apiculture has a major antagonist in Varroa destructor, the ectoparasitic mite that has become the most prominent driver of colony losses for the European honey bee, Apis mellifera. This was not always the case, as V. destructor is native to Asia and originally only infested the Asian honey bee, Apis cerana. As these two species have co-evolved, A. cerana colonies can coexist with the mite, in contrast to colonies of A. mellifera, which die within 2-3 years, unless treated. This review explores the differences in the coevolved and the novel parasite-host relationships and tries to determine what factors have made V. destructor so successful in A. mellifera. The resistance of A. cerana is multi-variate, but the two behaviors that are considered the most important are social apoptosis, which denies V. destructor from worker brood infestation, and grooming, which reduces mite populations when drone brood is not produced. A. mellifera lacks the former and is less effective at the later. Many effects of resistance behaviors and factors on varroa infestation are not quantified, making comparisons between them difficult. There are also many factors that remain largely unexplored by the scientific community such as entombing of drone brood, bee damage on mites, swarming, absconding and colony size, that could have an effect. This obscures what behaviors really have an effect in Varroa resistance. As we look into the future of the Varroa-honey bee relationship, there is hope in resistant variants of A. mellifera. However, whether resistant behaviors are compatible with market needs remains to be seen, as current treatments for Varroa control continue to be effective.